Qualitative Evaluation of Two Plant Extracts Vitexagnus and Dates Pollen to Some Sex Hormones Measurement in the Female Rats Induced by D-galactose - SuhaAllawi Hussein Almurumudhe; HayderAllawiHussein (Institute of Medico-legal Publications Pvt Ltd, 2021)
Vitexagnus-castus has long been used to treat female reproductive disorders and fertility in Europe for thousands of years. On the other hand, date palm pollen is a herbal combination in traditional medicines generally used to treat female and male fertility. Therefore, the present study aimed to evaluate these two plants qualitatively extracts VitexAgnus and dates pollen in female rats’ hormonal measurement. After exposure to D-galactose, 60 Sprague Dawley rats (180±15 gram) weight and three months ages were randomly distributed into six groups, ten rats received normal saline (control group), ten rats received 70% of the ethanolic extract of Vitex (group 2), ten rats received d-galactose (3 groups), ten rats received date pollen extract (4 groups), ten rats received d-galactose, and Vitex (5 groups), and finally ten rats received d-galactose and dates pollen extract (six groups). Animals from each group underwent a blood hormone test LH, FSH, Progesterone, and Estrogen by using immunological assay enzyme_lnkedimmunosorbent assay kits.The results found LH serum levels in the one group that received normal saline was significantly increased (P< 0.01) in the D-galactose groups, it significantly increased FSH serum levels in the control group that taken dates pollen (P< 0.01) rather than animals, which taken normal saline. Our results found a decrease in estrogen serum levels in the D-galactose groups rather than control groups. Finally, animals in the third group exposed to D-galactose at a dose rate on 500 mg/kg body weight for 30 days showed a significant decrease of Progestin level in serum of exposed rats. In conclusion: female hormonal measurement (LH) was increased, and (estrogen and progesterone) were dropped in the using date pollen. Otherwise, Vitexagnuscastus hasno significant differences in the LH and FSH serum levels.